Plasmon-enhanced electron harvesting in robust titanium nitride nanostructures - Doiron,B; Li,Y; Mihai,A; Bower,R; Alford,NM; Petrov,PK; Maier,SA; Oulton,RF (The Journal of Physical Chemistry Part C: Nanomaterials and Interfaces, 2019)
Titanium nitride (TiN) continues to prove itself as an inexpensive, robust, and efficient alternative to gold in plasmonic applications. Notably, TiN has improved hot electron-harvesting and photocatalytic abilities compared to gold systems, which we recently attributed to the role of oxygen in TiN and its native semiconducting TiO2–x surface layer. Here, we explore the role of localized surface plasmon resonances (LSPRs) on electron harvesting across the TiN/TiO2–x interface and probe the resilience of TiN nanostructures under high-power laser illumination. To investigate this, we fabricate TiN strips, in which the lateral confinement allows for the polarization-selective excitation of the LSPR. Using ultrafast pump–probe spectroscopy, optical characterization, and Raman vibrational spectroscopy, we relate the differences and changes observed in the electron behavior to specific material properties. We observe plasmon-enhanced electron harvesting beyond what is expected resulting from the enhanced absorption of the plasmonic mode. We accredit this to the surface oxide damping the plasmon resonance, providing additional nonradiative loss channels. Subsequently, we show that low-power annealing of the surface oxide layer reduces the trap density at the interface and increases the initial harvested electron concentration. The unique properties of TiN make it important in the future development of plasmonic electron-harvesting applications.